Pendekatan Ionik dalam Menulis Struktur Lewis - Ahmad, Wan Yaacob; Zakaria, Mat (Universiti Putra Malaysia Press, 1997)
This article discusses a new approach for writing Lewis structures for molecules and polyatomic ions. Initially in the writing process, the surrounding atoms of a covalent species are treated as anions in their octet states, while the central atoms are treated as cations; both are attributed to the invocation of ionic aspects of covalent species. The writing process involves three steps, i.e. recognizing the central atom, assigning the charges on respective atoms and forming the bonds for the geometrical shape of the species. Thirteen examples of structures, viz. CH4 , 03, 20, BeCI2, AIF6 3-, SSF2, SOF4 , 102F2-, CIF4, 13-, XeOF4 , XeF4 and VOCI3, are presented in four categories based on the nature of the central atoms. In addition, aspects of understanding of resonance and predicting the molecular shapes about central atoms based on a knowledge of simple Lewis electronic configurations are outlined.